Barriers to counseling and education on hypertension prevention related to cardiovascular risks - Aulia Asman; Rizakiyah Rizakiyah; An Autika Asman (Jurnal Konseling dan Pendidikan, 2026)
Hypertension is one of the leading risk factors for cardiovascular disease, contributing to high rates of morbidity and mortality worldwide. This study aims to identify factors that hinder the implementation of counseling and education for hypertension prevention related to cardiovascular risk. The study employed a quantitative approach with a descriptive design. Data were collected through questionnaires administered to respondents who met the study criteria and were then analyzed using descriptive statistics to describe the distribution of each barrier. The results of the study indicate that barriers to the implementation of counseling and education are influenced by various factors, including healthcare workers’ time constraints, patients’ low knowledge and motivation, limited educational materials, communication barriers, and a lack of institutional support in terms of resources and policies. These factors contribute to the low effectiveness of information dissemination and the adoption of hypertension prevention behaviors by the community. This study concludes that improving the quality of counseling and education requires adequate resource support, enhanced competencies of healthcare workers in educational communication, the provision of appropriate educational materials, and the strengthening of institutional policies to support the sustainable implementation of hypertension prevention programs. These findings are expected to serve as a basis for developing more effective health promotion strategies to reduce the risk of cardiovascular disease.